Predawn leaf water potential of grapevines is not necessarily a good proxy for soil moisture - Groenveld, Thomas; Obiero, Charles; Yu, Yingxue; Flury, Markus; Keller, Markus (BMC plant biology, 2023)
In plant water relations research, predawn leaf water potential (Ψ ) is often used as a proxy for soil water potential (Ψ ), without testing the underlying assumptions that nighttime transpiration is negligible and that enough time has passed for a hydrostatic equilibrium to be established. The goal of this research was to test the assumption Ψ = Ψ for field-grown grapevines. A field trial was conducted with 30 different cultivars of wine grapes grown in a single vineyard in arid southeastern Washington, USA, for two years. The Ψ and the volumetric soil water content (θ ) under each sampled plant were measured multiple times during several dry-down cycles. The results show that in wet soil (Ψ >  - 0.14 MPa or relative extractable water content, θ > 0.36), Ψ was significantly lower than Ψ for all 30 cultivars. Under dry soil conditions (Ψ <  - 0.14 MPa or θ < 0.36) Ψ lined up better with Ψ . There were differences between cultivars, but these were not consistent over the years. These results suggest that for wet soils Ψ of grapevines cannot be used as a proxy for Ψ , while the Ψ = Ψ assumption may hold for dry soils.